TUBERCULOSIS AND ITS ASSOCIATION WITH CD4+T CELL COUNT AND VIRAL LOAD AMONG HIV POSITIVE PATIENTS IN A TERTIARY CARE HOSPITAL - JOSE, NIGEL; BULA, ARUNA; KUMARI, POOSAPATI RATNA; KAMALA, PUVVULA (International Journal of Current Pharmaceutical Research, 2024)
Methods: The present study was a prospective study conducted from April 2022 to March 2023 in 4551 patients. Samples of 238 patients newly diagnosed with HIV attending Integrated Counselling and Testing Centre (ICTC), Visakhapatnam, Andhra Pradesh, India and registered for Antiretroviral Therapy (ART) were taken. 5 ml of blood sample was collected aseptically and tested for HIV. The 238 HIV-positive samples were tested for CD4 counts at presentation and after 6 mo using flow cytometry (Sysmex Partec CyFlow Flow cytometer). They were further subjected to real-time RT-PCR to detect viral load at 6 mo follow-up. Results: Out of 238 HIV-positive cases, predominant gender being males with 140 (58.82%) and the predominant age group was 31-40 y. At 6 mo follow-up, 19 patients (8%) were diagnosed as having TB. The mean CD4 counts at baseline and after 6 mo of antiretroviral therapy (ART)) was 296±229 and 436±271 cells/mm3 (p value of<0.001) for entire study group. The mean baseline CD4 count in patients who were not diagnosed with TB at the time of follow-up and those who were diagnosed as having developed TB was 307±232 cells/mm3 and 167±135 cells/mm3 respectively. At six mo follow-up, 32(14.6%) HIV patients who did not develop TB and 8(42.1%) patients who developed TB still had their CD4 counts<200 cells/mm3. This was statistically significant with a p value=0.019. Significant difference was not found between the two subgroups as the HIV-only group had 192(87.7%) patients and 16(84.2%) patients from newly diagnosed TB patients had their viral loads below detection levels. Conclusion: low CD4 counts at the baseline was a high-risk factor for the development of tuberculosis in HIV patients. The viral load values at 6-month follow-up did not prove to be significantly linked to the development of tuberculosis.